DNA methylation maintains the CLDN1-EPHB6-SLUG axis to enhance chemotherapeutic efficacy and inhibit lung cancer progression - Wu, Jia-En (Theranostics, 2020)
The loss of cancer-cell junctions and escape from the primary-tumor microenvironment are hallmarks of metastasis. A tight-junction protein, Claudin 1 (CLDN1), is a metastasis suppressor in lung adenocarcinoma. However, as a metastasis suppressor, the underlying molecular mechanisms of CLDN1 has not been well studied. Methods: The signaling pathway regulated by CLDN1 was analyzed by Metacore software and validated by immunoblots. The effect of the CLDN1-EPHB6-ERK-SLUG axis on the formation of cancer stem-like cells, drug resistance and metastasis were evaluated by sphere assay, aldefluor assay, flow cytometry, migration assay, cytotoxicity, soft agar assay, immunoprecipitation assay and xenograft experiments. Furthermore, the methylation-specific PCR, pyrosequencing assay, chromatin immunoprecipitation and reporter assay were used to study the epigenetic and RUNX3-mediated CLDN1 transcription. Finally, the molecular signatures of RUNX3/CLDN1/SLUG were used to evaluate the correlation with overall survival by using gene expression omnibus (GEO) data. Results: We demonstrated that CLDN1 repressed cancer progression via a feedback loop of the CLDN1-EPHB6-ERK1/2-SLUG axis, which repressed metastasis, drug resistance, and cancer stemness, indicating that CLDN1 acts as a metastasis suppressor. CLDN1 upregulated the cellular level of EPHB6 and enhanced its activation, resulting in suppression of ERK1/2 signaling. Interestingly, DNA hypermethylation of the CLDN1 promoter abrogated SLUG-mediated suppression of CLDN1 in low-metastatic cancer cells. In contrast, the histone deacetylase inhibitor trichostatin A or vorinostat facilitated CLDN1 expression in high-metastatic cancer cells and thus increased the efficacy of chemotherapy. Combined treatment with cisplatin and trichostatin A or vorinostat had a synergistic effect on cancer-cell death. Conclusions: This study revealed that DNA methylation maintains CLDN1 expression and then represses lung cancer progression via the CLDN1-EPHB6-ERK1/2-SLUG axis. Because CLDN1 enhances the efficacy of chemotherapy, CLDN1 is not only a prognostic marker but a predictive marker for lung adenocarcinoma patients who are good candidates for chemotherapy. Forced CLDN1 expression in low CLDN1-expressing lung adenocarcinoma will increase the chemotherapy response, providing a novel therapeutic strategy.